Pelatihan Pembuatan Bahan Ajar Berbasis Artificial Intelligence Terhadap Guru di Kabupaten Jepara - Siswanto, Joko; Wiyaka, Wiyaka; Huda, Choirul (Education and Talent Development Center of Indonesia, 2025)
AI technology can help teachers design teaching materials that are more effective, efficient and interactive. Seeing this great potential, training in making AI-based teaching materials for teachers in Jepara is designed to introduce and facilitate the application of this technology in the learning process. This training equips teachers with basic skills in creating teaching materials using AI-based applications that can be adapted to curriculum needs and student characteristics. The training implementation uses the andragogy method which prioritizes an approach to producing AI-based teaching material products. A total of 83 participants have successfully completed the training and practice 100% and are ready to apply AI teaching materials in classroom learning.